2010
DOI: 10.2114/jpa2.29.29
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Gait Parameters while Walking with Varying Loads

Abstract: This study aimed to clarify the relationships between loads and gait changes and among gait parameters while walking with various loads. Fifteen healthy young male adults (mean age: 22.1Ϯ1.6 years) walked with four kinds of loads based on each subject's body mass (0, 20, 40, and 60% of body mass: BM) on his back. Walking speed, cadence, stance time, swing time, double support time, step length, step width, walking angle, and toe angle were selected as gait parameters.Walking speed, cadence, stance time, and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 22 publications
4
25
0
Order By: Relevance
“…Numerous back-loading studies have demonstrated decreases in self-selected walking speed in proportion to added mass, resulting in a fairly constant CoL and heat production independent of loads (Myles and Saunders, 1979; Haisman, 1988; Demura and Demura, 2010). Reducing preferred walking speed in response to loads may be explained by the fact that preferred speed appears to be selected partly based on minimizing lower limb muscle activation (Ackermann and Van den Bogert, 2010; Miller et al, 2012), as the extra muscle force required to carry loads is produced by the lower limb muscles (Ghori and Luckwill, 1985; Griffin et al, 2003; Demura and Demura, 2010). Here, preferred speed for unloaded walking was reasonably close to the SPMinCoT (within the fairly flat part of the CoT curve); as frontal loads increased, the preferred speed chosen by our participants was reduced significantly compared to SPMinCoT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous back-loading studies have demonstrated decreases in self-selected walking speed in proportion to added mass, resulting in a fairly constant CoL and heat production independent of loads (Myles and Saunders, 1979; Haisman, 1988; Demura and Demura, 2010). Reducing preferred walking speed in response to loads may be explained by the fact that preferred speed appears to be selected partly based on minimizing lower limb muscle activation (Ackermann and Van den Bogert, 2010; Miller et al, 2012), as the extra muscle force required to carry loads is produced by the lower limb muscles (Ghori and Luckwill, 1985; Griffin et al, 2003; Demura and Demura, 2010). Here, preferred speed for unloaded walking was reasonably close to the SPMinCoT (within the fairly flat part of the CoT curve); as frontal loads increased, the preferred speed chosen by our participants was reduced significantly compared to SPMinCoT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Gait properties were measured by a gait analysis system (Walk Way MG-1000, Anima, Japan) in reference to a previous study [11]. The MG-1000 with plate sensors can determine time, dimensions and the distance of the foot or feet when the foot touches its surface and can measure grounding/non-grounding on the bearing surface as an on/off signal.…”
Section: Methodsmentioning
confidence: 99%
“…During loaded walking, young adults show an increased spatio-temporal gait variability, double support time, decreased step length (Dames and Smith, 2015;Demura and Demura, 2010;Huang and Kuo, 2014;Qu and Yeo, 2011) and local dynamic stability in the anteriorposterior (Liu and Lockhart, 2013), medio-lateral, and vertical directions (Liu and Lockhart, 2013;Qu, 2013). Older adults have demonstrated a similar adaptation in spatio-temporal gait variables in loaded conditions with increases in double support time and step width (Kubinski and Higginson, 2012).…”
Section: Introductionmentioning
confidence: 98%